Media culture & society : an introduction - Hodkinson, Paul. (Los Angeles SAGE publications, 2011)
It provides international forum for the presentation of research and discussion concerning the media, including the newer information and technology, within their political, economic, cultural and historical contexts.
Existing both in print and electronic/E-resource.
Includes bibliographical references and index.
Keywords: Mass media; Mass media - social aspects; Popular culture